Socialization of Financial Statement Preparation Based on SAK EMKM in Pringgondani Tourism Village in Balikpapan - Ulfah, Yana; Set Asmapane; Khairin, Fibriyani Nur; Rezkiyanti, Nur Alfiah; Rizka Dwi Jayanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The Pasar Tumpah Pringgodani Tourism Village, located in the Gunung Binjai area, Teritip Village, East Balikpapan, has become one of the unique tourist destinations that attract public attention.  This market offers a variety of local products, especially traditional foods, that tantalize visitors' appetites.  Micro, small, and medium enterprises (MSMEs) are a common term in the economic landscape that refers to productive economic ventures owned by individuals or business entities in accordance with the criteria set by Law No. 20 of 2008.  The presence of micro, small, and medium enterprises (MSMEs) in Indonesia is indeed very significant.  Financial statements are information that contains the financial records of a company.  This report can serve as valid evidence to monitor the company's financial condition.  SAK EMKM stands for Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah Makro, which is specifically designed as a benchmark for financial accounting standards for MSMEs.  This community service activity is conducted under the title "Socialization of Financial Statement Preparation Based on SAK EMKM in Pringgondani Tourism Village, Balikpapan."  This community service activity is expected to help MSMEs in organizing their financial administration in a more structured manner, so that MSMEs can accurately understand their financial condition.  The availability of periodic financial reports for MSMEs will facilitate their access to funding from banks, which will ultimately encourage the development of MSMEs.